2017
DOI: 10.1111/apa.13782
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset neonatal sepsis is associated with a high heart rate during automatically selected stationary periods

Abstract: International audienceAIM: This study examined the heart rate variability characteristics associated with early-onset neonatal sepsis in a prospective, observational controlled study.METHODS: Eligible patients were full-term neonates hospitalised with clinical signs that suggested early-onset sepsis and a C-reactive protein of >10 mg/L. Sepsis was considered proven in cases of symptomatic septicaemia, meningitis, pneumonia or enterocolitis. Heart rate variability parameters (n = 16) were assessed from five-, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…This indicated that both LV and RV systolic and diastolic dysfunction in these infants were more sensitive to detect myocardial dysfunction through conventional echocardiography. A study conducted by Nguyen et al [17] examined the variability in heart rate of the infants that is associated with early onset of neonatal sepsis. The results revealed that early onset of neonatal sepsis have been associated with increased heart rate that is measured during randomly selected stationary periods.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that both LV and RV systolic and diastolic dysfunction in these infants were more sensitive to detect myocardial dysfunction through conventional echocardiography. A study conducted by Nguyen et al [17] examined the variability in heart rate of the infants that is associated with early onset of neonatal sepsis. The results revealed that early onset of neonatal sepsis have been associated with increased heart rate that is measured during randomly selected stationary periods.…”
Section: Resultsmentioning
confidence: 99%
“…Heart-rate variability reflects the heart's adaptation to internal and external stimuli and is measured by the variation in RR intervals from the ECG signal. Analysis methods of RR interval time series were chosen considering past results on neonatal sepsis (Nguyen et al, 2017). Time-domain analysis of HRV included the mean and standard deviation (SD) of RR duration, an index of global HRV, and the square root of the mean squared differences of successive RR intervals (rMSSD), mainly reflecting parasympathetic control.…”
Section: Heart-rate and Respiratory-rate Variabilitymentioning
confidence: 99%
“…The Poincaré plot further assessed short-term (SD1) and long-term (SD2) HRV. Acceleration capacity (AC) and deceleration capacity (DC) were computed as previously described (Nguyen et al, 2017). The scale invariance (self-similarity of RR time series) was tested through the detrended fluctuation analysis technique, using the fractal scaling exponent α1 (from 4 to 40 beats) (Al-Omar et al, 2019).…”
Section: Heart-rate and Respiratory-rate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Times between consecutive R waves (RR) (which measures cardiac cycle length) were manually verified. Parameters were selected based on studies showing changes in infants with sepsis (inflammation) or after immunization and were studied as previously reported [7][8][9] . The variables studied were the mean cardiac cycle length (mean), the standard deviation (SD) which measures the magnitude of global heart rate variability, and the square root of the mean squared differences of successive RR intervals (rMSSD; short-term beat-to-beat variability which reflects parasympathetic control).…”
Section: Assessment Of Heart Rate Variabilitymentioning
confidence: 99%